Impending Effects of Basel III in the BRICS Economies - Hossain, Md. Zakir (Curtin University, 2016)
This thesis addresses the concerns whether the universal rules of Basel III would be able to protect banks and ensure macroeconomic benefits in the BRICS economies. The empirical evidence shows that the Basel III regulation is effective in increasing the resilience of banks. The regulation increases GDP albeit with some macroeconomic costs. However, the net benefits are positive. Thus, it seems worthwhile to adopt and implement the Basel III regulation in the BRICS economies.